KETERDAPATAN BAHAN GALIAN GALENA DI DAERAH CIGEMBLONG, KABUPATEN LEBAK, PROPINSI BANTEN - -, Mega Fatimah Rosana; -, Euis Tintin Yuningsih; -, Adi Hardiyono (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
The objective of the research is to identified and investigated the occurrence of lead, its distribution, size, formation, quantity and quality in the district of Cigemblong, regency of Lebak, province of Banten as a guide for advance investigation. Several samples collected and analyzed petrographically to identified rock, alteration and ore mineral variation as well as geochemistry analysis by XRF method.The stratigraphic units of the research area can be classified into three rock units, such as from oldest to youngest one are carbonaceous claystone, tuf, andesitic – dioritic intrusive, and volcanic breccia units. Three alteration types in the research are are prophylitic, argillic, and silicification alteration.Field investigation concluded that mineralization occurred as mineralization zone of quartz veins with N – S and NE – SW direction, partially as thin lensing in claystone unit. Otherwise the distribution are limited, and separated each other. So, it is difficult to trace the vein zone and lensing as same vein.The characteristic of the mineralization zone gangue minerals dominated composed of quartz, calcite and clay mineral, with ore minerals of pyrite